Trade openness, foreign direct investment and growth in Thailand - Yusoff, Mohammed; Nuh, Ruslee (2011)
This study attempts to examine the relationship among trade openness, foreign direct investment, gross domestic investment, and economic development in Thailand using co-integration test, Granger causality test, and variance decomposition analysis. The cointegration analysis suggests that the variables are cointegrated and there exists a unique long-run relationship among the variables. The results of Granger causality test show that trade openness, foreign direct investment and gross domestic investment Granger caused economic growth unidirectionally, except trade openness. The variance decomposition analysis indicates that foreign direct investment seems to be the most important determinant of Thailand’s real GDP per capita growth, followed by trade openness and gross domestic investment. This suggests that policy makers in Thailand should liberalize its economy to encourage foreign trade and foreign direct investment inflows to achieve a sustained high economic growth.